CD30 Expression in Pediatric Neoplasms, Study of 585 Cases. (June 2017) - Cheng, Jinjun; Zhu, Haiqing; Choi, John Kim
CD30 is a member of the tumor necrosis factor receptor superfamily, member 8 (TNFRSF8), and its normal expression is restricted to activated T and B cells. In tumor cells, CD30 expression is most commonly associated with lymphoid malignancies (Hodgkin and non-Hodgkin lymphomas) and is a therapeutic target using anti-CD30 antibody. CD30 expression has been reported also in mostly adult non-lymphoid malignancies, raising the possibility of CD30-targeted therapy for additional tumors. In this study, we examined the incidence of CD30 expression in 251 hematopoietic and 334 non-hematopoietic cases of pediatric tumors. As expected, strong and membranous CD30 staining was seen in anaplastic large cell lymphoma, classical Hodgkin lymphoma, and embryonal carcinoma while variable staining was seen in diffuse large B cell lymphoma. In addition, positive CD30 staining was also seen in cases of neuroblastoma (33 of 56), neoplasm with chondroid differentiation (8 of 25), myeloid neoplasms (11 of 120), hemangioma (2 of 12), and mature teratoma (1 of 11). In neuroblastoma, the CD30 expression was generally restricted to cells with ganglion differentiation; staining of ganglion cells was also seen in the one positive case of mature teratoma. In neoplasm with chondroid differentiation, the positive cases were chondrosarcoma (3 of 5), chondroblastic osteosarcoma (2 of 10), and chondroblastoma (3 of 7). In acute myeloid leukemia, the CD30 positive cases were more common in AML with monocytic differentiation but did not correlate with any specific molecular change. We conclude that CD30 expression in pediatric tumors is more general than anticipated and future studies are warranted to understand the biologic and therapeutic significances.